AN ANALYSIS OF SLANG WORDS IN THE BASKETBALL DIARIES MOVIE - Nasution, Dini Fitriani; Kristiana, Vera (IKIP Siliwangi, 2024)
The objective of the problem was to analyze the types of slang words and the their meanings containes in the film The Basketball Diaries. This type of research was descriptive qualitative, it systematically described the data of slang words found in the film. The research discussed 2 types of slang words, namely primary and secondary with their meanings. The film consisted 9 scenes. The findings that researchers obtained in the film ever were 63 slang words which were primary slang and 39 slangs words which were secondary slang and the meanings contained in them such as callstoaction, insulting words, expressing opinions, mentioning drugs and describing a person’s character.